EFFECT OF GIVING PAPAYA LEAF JUICE (Carica papanya L.) FERMENTED THROUGH DRINKING WATER AGAINST THE PHYSICAL COMPOSITION OF THE SUPERIOR CHICKEN CARCASS BALITBANGTAN (KUB) - R.A., Sudekno,; Ariana, I N.T.; Ardika, I N. (Jurnal Peternakan Tropika, 2024)
This study aims to determine whether the administration of 2% - 6% fermented papaya leaf (Carica papaya L.) juice through drinking water can improve the physical composition of KUB chicken carcasses. The research was conducted over 8 weeks in Demung Village, Kediri, Tabanan. The experimental design used was a completely randomized design (CRD) with 4 treatments and 4 replications. Each replication used 3 homogeneous weight KUB chickens. A total of 48 KUB chickens were used in the study. The treatments were as follows P0: Chickens without fermented papaya leaf juice (control), P1: Chickens given 2% fermented papaya leaf juice, P2: Chickens given 4% fermented papaya leaf juice, and P3: Chickens given 6% fermented papaya leaf juice. The observed variables were slaughter weight, carcass weight, carcass percentage, meat percentage, bone percentage, and subcutaneous fat percentage, including skin. Based on the results of this study, it can be concluded that the administration of 2%-6% fermented papaya leaf juice through drinking water had no significant effect (P>0.05) on slaughter weight, carcass weight, carcass percentage, and physical composition of the carcass. Based on the results of the study, it is recommended that administering 2% fermented papaya leaf juice in the drinking water of KUB chickens can yield optimal results by increasing slaughter weight, carcass weight, bone percentage, and reducing subcutaneous fat/skin percentage.